PENGARUH SARANA DAN PRASARANA TERHADAP SEMANGAT DAN HASIL BELAJAR MAHASISWA IKIP SILIWANGI BANDUNG - Sinta Nuri; Fitri Nuraini; Indra Permana (IKIP Siliwangi, 2018)
To adequate facilities and infrastructure is an effort to build the spirit of learners to be more eager to do positive things in education. Many learners have very good potential and a great hidden talent, but can not develop it maximally because of the limited facilities owned by the school or campus. Facilities and infrastructure also affect the spirit and interest in learning of the learners, because of the lack of adequate facilities and infrastructure, will trigger low learning spirit of learners. In this research the researcher use descriptive qualitative method. It is a method that aims to describe how the situation and the actual phenomenon, then described in the research report. Intruments collection Data collected by spreading questionnaires through google form to some students IKIP Siliwangi Bandung. Of the 35 respondents almost 50% argued that supporting facilities in activities outside the academic is more limited than the facilities supporting activities in academic.